1996
DOI: 10.1079/bjn19960144
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of breakfast to the diets of a sample of 136 primary-schoolchildren in Edinburgh

Abstract: The contribution of breakfast to mean daily energy and nutrient intakes was investigated in a sample of 7-8-year-old children recruited by letter from five Scottish schools. After eighteen families dropped out of the study and three dietary records were discarded, the final sample numbered 136 (51 %). Dietary data were collected using the 7 d weighed inventory, while a questionnaire was used to classify children into manual or non-manual social class groups. Mean daily energy intakes were close to estimated av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 13 publications
3
59
1
Order By: Relevance
“…Since the numbers consuming breakfast are likely to drop as they get older, especially in girls (Ruxton et al, 1996;Hackett et al, 2002), it is important to motivate this age group to encourage them to continue to eat breakfast. A notable determinant of this group's eating behaviour was the arrival of the weekend when their diets changed dramatically; breakfast was frequently missed in favour of time in bed, take-aways became a more regular feature of the diet and boredom and increased leisure time promoted an increase in food consumption in general.…”
Section: Discussionmentioning
confidence: 99%
“…Since the numbers consuming breakfast are likely to drop as they get older, especially in girls (Ruxton et al, 1996;Hackett et al, 2002), it is important to motivate this age group to encourage them to continue to eat breakfast. A notable determinant of this group's eating behaviour was the arrival of the weekend when their diets changed dramatically; breakfast was frequently missed in favour of time in bed, take-aways became a more regular feature of the diet and boredom and increased leisure time promoted an increase in food consumption in general.…”
Section: Discussionmentioning
confidence: 99%
“…breakfast behaviours (Affenito, 2007;Aranceta et al, 2001;Kuczynski et al, 2007;Ruxton et al, 1996;Utter et al, 2007) whereas two studies reported that breakfast consumption was related to gender (Shaw, 1998) and behavioural changes (Siega-Riz et al, 1998) and that socio-economic patterns had minimal bearing on breakfast eating patterns (Shaw, 1998;Siega-Riz et al, 1998).…”
Section: Proportion Of Breakfast Skippersmentioning
confidence: 99%
“…Nine of the studies were analyses from second-hand survey data in which aspects of a larger survey were used as the data for the study (Baric & Satalic, 2002;Barton et al, 2005;Haines et al, 1996;Kuczynski, Cleveland, Goldman, & Moshfegh, 2007;Song, Chun, Obayashi, Cho, & Chung, 2005;Sungsoo, Dietrich, Brown, Clark, & Block, 2003;Utter et al, 2007;Williams, 2007;Wilson, Parnell, Wohlers, & Shirley, 2006 Maeyer, & De Backer, 2007;Morgan, Zabik, & Stampley, 1986;Mullie et al, 2006;Ortega et al, 1996;Ruxton, O'Sullivan, Kirk, Belton, & Holmes, 1996;Shaw, 1998;Siega-Riz, Popkin, & Carson, 1998;Timlin, Pereira, Story, & Neumark-Sztainer, 2008). …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, breakfast cereals are usually consumed with milk, which is a significant source of calcium and riboflavin, and this is likely to be an important determinant of the higher calcium and riboflavin intake reported among consumers. Consumption of breakfast cereals is associated with higher intakes of several micronutrients in preschool children (Ruxton and Kirk, 1997), school children and adolescents (Crawley, 1993;Nicklas et al, 1993Nicklas et al, , 1995Gibson and O'Sullivan, 1995;Ruxton et al, 1996;Van den Boom et al, 2006;Williams, 2007;Deshmukh-Taskar et al, 2010), and adults (McNulty et al, 1994). Breakfast consumption is also associated with higher intakes of fibre (Ruxton and Kirk, 1997;Barton et al, 2005;Rampersaud et al, 2005;Van den Boom et al, 2006).…”
Section: Introductionmentioning
confidence: 99%